PDB, Pertumbuhan dan Pembangunan Ekonomi Di Indonesia - ., Yanuar (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2010)
Gross Domestic Product (GDP) of a country is calculated by using the production approach and influenced by the capital, human resources, natural resources, and entrepreneurship. Indonesia with the four most tremendous amounts of resources in the word has actually a potential to be a rich nation which is able to improve its people walfare. But seen from its GDP aspect, Indonesia is only at number 142 in the word.